Larger Than Life: Isolation and Genomic Characterization of a Jumbo Phage That Infects the Bacterial Plant Pathogen, Agrobacterium tumefaciens - Attai, Hedieh; Boon, Maarten; Phillips, Kenya; Noben, Jean-Paul; Lavigne, Rob; Brown, Pamela J. B. (Frontiers in Microbiology, 2018)
Agrobacterium tumefaciens is a plant pathogen that causes crown gall disease, leading to damage of agriculturally-important crops. As part of an effort to discover new phages that can potentially be used as biocontrol agents to prevent crown gall disease, we isolated and characterized phage Atu_ph07 from Sawyer Creek in Springfield, MO, using the virulent Agrobacterium tumefaciens strain C58 as a host. After surveying its host range, we found that Atu_ph07 exclusively infects Agrobacterium tumefaciens. Time-lapse microscopy of A. tumefaciens cells subjected to infection at a multiplicity of infection (MOI) of 10 with Atu_ph07 reveals that lysis occurs within 3 h. Transmission electron microscopy of partially purified virions shows that Atu_ph07 has a typical Myoviridae morphology with an icosahedral head (147 nm), long tail (130 nm), and tail fibers. The sequenced genome of Atu_ph07 is 490 kbp, defining it as a jumbo phage. The Atu_ph07 genome contains 714 open reading frames (ORFs), including 390 ORFs with no discernable homologs in other lineages (ORFans), 214 predicted conserved hypothetical proteins with no assigned function, and 110 predicted proteins with a functional annotation based on similarity to conserved proteins. The proteins with predicted functional annotations share sequence similarity with proteins from a broad range of microbes including bacteriophages and bacteria. The functionally annotated genes are predicted to encode DNA replication proteins, structural proteins, lysis proteins, proteins involved in nucleotide metabolism, and tRNAs. Characterization of the gene products reveals that Atu_ph07 encodes homologs of sixteen T4 core proteins and is closely related to Rak2-like phages. Using ESI-MS/MS, the majority of predicted structural proteins could be experimentally confirmed and 112 additional virion-associated proteins were identified. The genomic characterization of Atu_ph07 suggests that this phage is lytic and the dynamics of Atu_ph07 interaction with its host indicate that this phage may be suitable for inclusion in a phage cocktail to be used a biocontrol agent.